Developing Electrical Magnetic Textbook Based On Technological Pedagogical Content Knowledge (TPCK) (Jurnal Pendidikan Fisika, 2021)
Electrical magnetic is a compulsory subject in the physics education program. One of the learning outcomes and graduates in the curriculum is to be able to analyze subject matter (pedagogical content knowledge). Researcher's observations during giving lectures on magnetic electricity showed that students paid less attention to the importance of understanding on the relationship between learning outcomes and teaching material during lectures. Thus, this phenomenon is appointed as one of the lecture evaluations in the study program. The lecture’s evaluation results in a recommendation to develop textbooks that are adjusted in learning outcomes and graduates that refer to the curriculum of the physics education program. It is not enough to stop here, the problem findings continue for online learning related to Work From Home policies during the pandemic. This of course requires the availability of references that can be open accessed. Hence, the researchers then attempted to develop electrical magnetic textbook based on PCK (pedagogical content knowledge) which contained material content and material content analysis according to learning outcomes and graduates in the curriculum of the Physics Education. This study aims to :  (1) determine the feasibility of electrical magnetic textbook based on PCK according to experts. (2) determine the  responses of students after using electrical magnetic textbook based on PCK. The research method uses research and development design by gathering information stages and references, designing, developing, product, validating, and revising the product. The research was conducted in 2020 in the physics education study program IKIP PGRI Pontianak. Data collection techniques are in the form of indirect communication techniques. Overall, electrical magnetic textbook based on PCK have been produced. The validation results show that textbooks have an average validation score of 77.77% with Eligible criteria. The students’ responses analysis show that textbooks developed have an average score of 78.52% with high criteria. After the revision, the textbook was presented with an online ISBN and open access on the online media